Prostaglandin E2 Induces Expression of Mineralization Genes by Undifferentiated Dental Pulp Cells - Lorencetti-Silva,Francine (2019)
Abstract Prostaglandin E2 (PGE2) is a lipid mediator usually released during inflammation. This study aimed to investigate the potential of soluble or microsphere-loaded PGE2 on inducing differentiation of dental pulp stem cells. PGE2-loaded microspheres (MS) were prepared using an oil-in-water emulsion solvent extraction-evaporation process and were characterized. Mouse dental pulp stem cells (OD-21) were stimulated with soluble or PGE2-loaded MS (0.01 and 0.1 µM). Cell viability was determined by MTT colorimetric assay. Ibsp, Bmp2 and Runx2 expression was measured by quantitative reverse transcription polymerase chain reaction (qRT-PCR) after 3, 6, and 24 h. The results showed that the soluble PGE2 reduced dental pulp stem cells viability after 24 h of stimulation whereas PGE2-loaded MS did not. Soluble PGE2 up-regulated Ibsp and Bmp2 at 3 h, differently from PGE2-loaded MS. On the other hand, PGE2-MS induced Bmp2 and Runx2 at 6 h and Ibsp at 24 h. In conclusion, our in vitro results show that PGE2, soluble or loaded in MS are not cytotoxic and modulateIbsp,Bmp2, andRunx2gene expression in cultured OD-21 cells.